Stock market scams, shell companies, penny shares, boiler rooms and cold calling: the UK experience - Barnes, Paul (International journal of law, crime and justice, 2017)
This paper examines the fraudulent sale of stocks and shares in shell companies by boiler rooms in order to defraud UK investors. It examines the law, the way boiler rooms are organised, the types of companies and scams used, and the markets involved including penny shares, US Regulation S stocks and the Over-the-Counter markets. It also examines the record of the UK regulators, primarily the Financial Conduct Authority (previously the Financial Services Authority) in acting against firms and individuals they had ‘authorised’, and other prosecutors in criminal actions against the perpetrators (usually unauthorised brokers running boiler rooms). The paper makes the point that whilst the public purse bears the costs of prosecution and compensation, the quasi-regulators (the professionals adding credence to a scheme) have rarely been pursued either as parties to a fraud or sued for negligence.